2014
DOI: 10.1186/1742-9994-11-49
|View full text |Cite
|
Sign up to set email alerts
|

Are antimicrobial defences in bird eggs related to climatic conditions associated with risk of trans-shell microbial infection?

Abstract: IntroductionAll bird eggs are exposed to microbes in the environment, which if transmitted to the developing embryo, could cause hatching failure. However, the risk of trans-shell infection varies with environmental conditions and is higher for eggs laid in wetter environments. This might relate to generally higher microbial abundances and diversity in more humid environments, including on the surface of eggshells, as well as the need for moisture to facilitate microbial penetration of the eggshell. To protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 76 publications
2
17
0
Order By: Relevance
“…However, we did not observe changes in egg white pH in altricial eggs resulting from different incubation patterns. As a similar trend with a rather slight decrease of egg white pH along with incubation cycle has been documented in studies on altricial eggs of the family Alaudidae (Horrocks et al, 2014;Grizard et al, 2015), this suggests that the effect of incubation pattern on egg white pH is likely to be species specific across the avian precocial-altricial spectrum.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, we did not observe changes in egg white pH in altricial eggs resulting from different incubation patterns. As a similar trend with a rather slight decrease of egg white pH along with incubation cycle has been documented in studies on altricial eggs of the family Alaudidae (Horrocks et al, 2014;Grizard et al, 2015), this suggests that the effect of incubation pattern on egg white pH is likely to be species specific across the avian precocial-altricial spectrum.…”
Section: Discussionsupporting
confidence: 80%
“…It is therefore obvious that many other factors such as ambient temperature (Saino et al, 2004;Horrocks et al, 2014), nest humidity (Wellman-Labadie et al, 2008c), laying sequence and stage of breeding season (Saino et al, 2002;Bonisoli-Alquati et al, 2010) or individual intrinsic factors (D'Alba et al, 2010b) affect the deposition and/or activity of egg white AMPs. As we used two representative altricial and precocial model species bred under relatively controlled conditions, we can exclude these potentially confounding factors in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial infection of eggs can drastically reduce clutch viability and, once pathogens pass through the membrane and infect the developing embryo, there is typically a low chance of survival (Kiesecker and Blaustein, 1997, Adamo, 1999, Cook et al, 2003, Brandl et al, 2014. A robust antimicrobial defense is therefore fundamental to the health of developing embryos (Shawkey et al, 2008, Horrocks et al, 2014. Python embryos at oviposition are approximately one-third through development (Lourdais et al, 2008) and have fully functional livers, which is primary source of synthesis for antimicrobial peptides (van Hoek, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Results from studies that used similar immune indices to the ones used in this study are equivocal: a study 30 on different species of adult larks (Alaudidae) along an aridity gradient spanning desert, temperate and tropics showed negative correlations between aridity and haemagglutination and haemolysis titres, and haptoglobin concentration, but no correlations between aridity and ovotransferrin concentration. However, another study 83 on antimicrobial proteins in eggs from larks in different environments showed contrasting patterns between ovotransferrin and lysozyme concentration in egg albumen. Elsewhere in the tropics, a study 21 on chicks of Red-capped Larks Calandrella cinerea from three climatically distinct locations in Kenya recorded no differences between immune indices, even though these chicks showed significant differences in growth patterns.…”
Section: Discussionmentioning
confidence: 95%
“…S1-5). Studies involving larger latitudinal gradients show that mean annual temperature seems to explain variation in parasite load and immune indices better than precipitation 19,83 . Results from studies that used similar immune indices to the ones used in this study are equivocal: a study 30 on different species of adult larks (Alaudidae) along an aridity gradient spanning desert, temperate and tropics showed negative correlations between aridity and haemagglutination and haemolysis titres, and haptoglobin concentration, but no correlations between aridity and ovotransferrin concentration.…”
Section: Discussionmentioning
confidence: 99%